Effect of Temperature and Salinity on Survival and Growth of Artemia franciscana from Basrah, Iraq - Abdullah, Dawood S.; Salman, Salman D.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
Laboratory experiments were carried out to express the effects of temperature, salinity and the combined effects of temperature–salinity on survival, growth and biomass of Artemia franciscana at 5 temperatures: 10, 20, 25, 30 and 35 ºC and 5 salinities: 35, 55, 75, 95 and 115 ‰. Temperature of 20 ºC and salinity of 55 ‰ showed best survivals (93 %), biomass (122.87 mg DW/L) and high growth (4.94 mm), whereas at 30 ºC and salinity of 95 ‰, the least survivals (21 %) was attained. However, the highest average growth was 6.1 mm attained at 30 ºC and 115 ‰, and the lowest growth was 1.49 mm at 10 ºC and 95 ‰, meanwhile, the lowest average biomass was 3.79 mg DW/L at 10 ºC and 115 ‰. Apparently, temperature of 20 ºC and salinity of 55 ‰ is the best combination for the local strain of A. franciscana from Basrah and is recommended for mass culture of this strain.